Cosmological parameters and non-vacuum initial states - Scóccola, Claudia Graciela (2007)
A class of spatially flat models with a cosmological constant and a primordial broken scale invariant (BSI) spectrum of adiabatic perturbations is confronted with the most up-to-date observational data of CMB and matter power spectrum. The theoretical model includes a parameter nb for the number of quanta in the non–vacuum initial state, and a privileged scale leading to the existence of a feature in the primordial power spectrum. This feature is located at comoving wavenumber kb and its profile is characterized by a step in k with steepness α, the full set {nb, kb, α} being taken as free parameters in our numerical study. We present here preliminary results of a detailed Markov Chain Monte Carlo analysis with CAMB and CosmoMC of the latest CMB and P(k) measurements, including the 3-year WMAP and the final 2dFGRS catalogue, where we derive joint constraints on eight out of the many relevant primary parameters –both cosmological and feature– of our BSI adiabatic model.